Under armour equity research - Giovanni, Fabio Di (2022)
A firm's value is determined using a variety of ways that allow for a better understanding of how the company operates and what the company's future development goals are based on future trends that allow for forecasting the future. With this report we aim to estimate the value of the stocks of Under Armour on the 31stof December 2022.The Discounted Cash Flow (DCF) was the method principally employed for this evaluation, together with a Multiple Assessment. The conclusion of the DCF valuation shows that the market under Armour is underrated at $29.69 as a target price, compared with$20.56 as at 12/2021. The Under Armour Equity Approval Recommendation is hence a BUY Recommendation.